The influence of plantar short foot muscle exercises on foot posture and gait parameters in long-distance runners - Sulowska, I.; Mika, A.; Oleksy, L. (Journal of Kinesiology and Exercise Sciences, 2017)
Aim: The aim of this study was to evaluate the influence of exercises of plantar short foot muscles on foot posture and gait parameters in long-distance runners. Basic procedures: The study involved 48 long-distance runners aged 21-45 years. The runners performed the short foot muscle exercises daily for 6 weeks. The Foot Posture Index (FPI-6) and gait parameters (G-walk) were measured twice: at baseline and after 6 weeks of exercises. Results: Lower values of the Foot Posture Index (FPI-6) were observed. In the assessment of gait parameters runners obtained lower cadence, walking speed, stride length and % stride length/height. Gait cycle duration was increased. Conclusions: Exercises strengthening short foot muscles have beneficial effect on foot alignment by change of foot posture from a slight pronation towards a neutral foot. Change of gait parameters may indicate on improvement of motor control and shift natural and comfortable walking speed towards lower values. The short foot muscle exercises should be included as a part of daily training programme of runners.